Trends on Rice Production and Productivity in India and the North East Region : Issues and Challenges - Imnawapang Longkumer, B.; Giribabu, M. (Arthshastra Indian Journal of Economics & Research, 2019)
The study highlighted the trends in area, production, and productivity of rice cultivation in India and the North East Region and tried to investigate the major issues and challenges of rice cultivation. The data from the years 1997-98 to 2015-16 were collected from sources such as Handbook of Statistics, Directorate of Economics and Statistics, Ministry of Agriculture, Govt. of India and The North Eastern Development Finance Corporation Ltd. (NEDFi) databank. The study revealed that the area, production, and productivity in India witnessed an increasing trend at a lower rate of about 0.99%, 1.24%, and 5.94%, respectively. However, in case of the North East Region, there was an increasing trend in area and productivity by about 0.18% and 1.07%, which was much lower than the national average, while production was 2.05%. The study showed that there was a fluctuating trend in area, production, and productivity in India and the North East Region over this period. Lack of advanced machinery, floods, infestation by weeds and pests, non-availability of HYV seeds, discouraging price conditions are some limiting factors for the rice growers, weaning them away from rice cultivation in India in general and the North East Region in particular.